2020
DOI: 10.1089/jmf.2019.0172
|View full text |Cite
|
Sign up to set email alerts
|

Virgin Coconut Oil Associated with High-Fat Diet Induces Metabolic Dysfunctions, Adipose Inflammation, and Hepatic Lipid Accumulation

Abstract: Obesity reaches an epidemic level worldwide, and this condition is associated with chronic low-grade inflammation and secondary comorbidities, largely driven by global changes in lifestyle and diet. Various dietary approaches are proposed for the obesity treatment and its associated metabolic disorders. Good taste, antioxidant functions, and vitamins have been attributed to virgin coconut oil (VCO). However, VCO contains a large amount of saturated fatty acids, and the consumption of this fat is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 60 publications
6
36
0
Order By: Relevance
“…On the contrary, saturated fatty acids trigger a TLR4-mediated inflammatory response [44,45]. A recent study demonstrated that virgin CO is associated with high-fat diet-induced metabolic alterations and adipose inflammation in rats [46]. Similarly, the present study showed the negative effect of CO supplementation to sows on LPS-induced mammary inflammation.…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, saturated fatty acids trigger a TLR4-mediated inflammatory response [44,45]. A recent study demonstrated that virgin CO is associated with high-fat diet-induced metabolic alterations and adipose inflammation in rats [46]. Similarly, the present study showed the negative effect of CO supplementation to sows on LPS-induced mammary inflammation.…”
Section: Discussionsupporting
confidence: 74%
“…For example, coconut oil increased adiposity and AT inflammation in C57BL/6J mice [ 35 ]. In addition, virgin coconut oil supplementation increased adipocyte hypertrophy and promoted AT inflammation in rats [ 36 ]. On the other hand, in another study, virgin coconut oil has been shown to reduce adiposity and AT inflammation in BALB/c mice fed a high-refined carbohydrate-containing diet [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The weight reduction effects of other remedies, that are widely used, were not studied previously such as parsley, grape fruit, rose water, apple cider vinegar, bitter almond, nettle leaf, eleuthero root, dandelion leaf, marshmallow root, slippery elm bark, papaya leaf, balsamic vinegar, and bitter orange. In addition, some of the remedies were reported to have severe side effects as coconut [23], senna [24], and bitter orange [25]. Finally, it is important to highlight that herbal and home remedies differ widely from one place to another depending on society culture, endogenous weather, and available medicinal plants.…”
Section: Discussionmentioning
confidence: 99%